Processamento e caracterização de farinha obtida a partir de subprodutos de melão (Cucumis Melo. L): potencial aplicação em pão sem glúten - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Brazil is the third largest fruit producer in the world, and the growing production of melon (Cucumis Melo L.) is associated with its health benefits. However, the high production of fruits generates large volumes of by-products such as peels and seeds, which do not have an appropriate destination. The use of peels and seeds in the preparation of new products may be the solution, for example, the production of unconventional flours, which stand out as a healthy and nutritious alternative, especially for people with celiac disease. In this context, this study aims to prepare flours from yellow melon by-products to be used in the formulation of gluten-free and added sugar-free bread. The melon peels and seeds were subjected to two drying processes, in an oven with forced air circulation (70°C for 24h) and in a vacuum oven (70°C for 29h), after which they were milled and sieved. The flours were analyzed for their centesimal composition and compared for their dietary fiber content and antioxidant activity to choose the best drying method. In addition, analyses of granulometric characterization, water activity and pH were performed on the flour that presented the best results. Afterwards, three formulations were prepared with gluten-free flours (rice and sweet cassava starch), two of which were partially replaced by melon by-product flour obtained from an oven with forced air circulation: FA (Control Formulation), FB (25% replacement) and FC (50% replacement). The breads were evaluated for texture, color, specific volume and nutritional table. As a result, it was found that the flour obtained by drying in an oven with forced air circulation presented better results in the centesimal composition, in addition to greater antioxidant capacity. The values of moisture, ash, proteins, lipids, dietary fiber, carbohydrates and antioxidant activity were 5.57%, 9.40%, 14.78%, 11.83%, 48.91%, 9.51% and 18.35 µmol Trolox/g of sample, respectively. The flour presented positive results for granulometric characterization, water activity and pH, being 235 µm; 0.8 and 4.89, respectively. The FA, FB and FC breads obtained a specific volume of 2.19, 1.75 and 1.56 mL/g, respectively. The difference in specific volume is related to the high fiber content present in the melon by product flour. The texture analysis indicated that replacing conventional gluten-free flours with melon by-product flour can result in firmer and denser breads due to the high fiber content of this flour. The color analysis showed that melon by-product flour can make the color of the breads darker, which indicates healthier breads. The nutritional table of the breads demonstrates that melon by-product flour has high potential to improve the nutritional value of the formulations. Therefore, using melon by-products to produce flour for bakery products is an efficient alternative to improve the nutritional quality of gluten-free breads.
Keywords: Fibras alimentares; Composição centesimal; Antioxidante; Celíacos; Co - produto; Dietary fiber; Centesimal composition; Antioxidant; Celiac; Co-product; CNPQ::ENGENHARIAS